2010
DOI: 10.1016/j.neuroimage.2010.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of normal ageing on white matter structure using unsupervised tract shape modelling

Abstract: Quantitative tractography may provide insights into regional heterogeneity of changes in white matter structure in normal ageing. Here we examine how brain atrophy and white matter lesions affect correlations between tract shape, tract integrity and age in a range of frontal and non-frontal tracts in 90 non-demented subjects aged over 65 years using an enhanced version of probabilistic neighbourhood tractography. This novel method for automatic single seed point placement employs unsupervised learning and stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…36 Tractaveraged water diffusion parameters were obtained using a fully automated tract segmentation technique, PNT, which removes the dependence of tractography output on the potentially subjective placement of seed points within tracts of interest. 21,23 Although atrophy and WML volumes were obtained using a validated semiautomatic method, 26 such methods are insensitive to subtle visually detectable variations and lack of specificity in expressing rele- vant information like lesion location. Qualitative measures are therefore sometimes preferred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Tractaveraged water diffusion parameters were obtained using a fully automated tract segmentation technique, PNT, which removes the dependence of tractography output on the potentially subjective placement of seed points within tracts of interest. 21,23 Although atrophy and WML volumes were obtained using a validated semiautomatic method, 26 such methods are insensitive to subtle visually detectable variations and lack of specificity in expressing rele- vant information like lesion location. Qualitative measures are therefore sometimes preferred.…”
Section: Resultsmentioning
confidence: 99%
“…Tract-averaged ͳDʹ and FA values, weighted by the connection probability, were determined for 12 tracts of interest using probabilistic neighborhood tractography (PNT) with the BedpostX/ProbTrackX algorithm, 20 a novel approach for automatic segmentation of major white matter pathways. [21][22][23][24][25] Tracts assessed were the genu and splenium of corpus callosum, bilateral anterior thalamic radiations, rostral cingulum bundles, and bilateral arcuate, uncinate, and inferior longitudinal fasciculi.…”
mentioning
confidence: 99%
“…However, additional studies have verified the global decline of FA with age (Hsu et al 2010), with an antero-posterior gradient of susceptibility Minati et al 2007). Moreover, DTI studies that examined the effects of WMH, ventriculomegaly, and brain atrophy found these to contribute to a decline of FA with age (Bastin et al 2010). Although WM lesions with age are exacerbated by hypertension, these appear in more posterior regions, a pattern distinct from normal aging (Kennedy and Raz 2009a).…”
Section: Diffusion Tensor Imaging In Humansmentioning
confidence: 97%
“…The developing/aging brain, in particular, has been the research topic of many investigations, 1 with studies including subjects ranging from neonates to aging adults. It has been shown repeatedly that the FA of several WM regions (e.g., the cingulum bundles and the uncinate fasciculi) increases during maturation and subsequently decreases with age above the age of approximately 30 years (Bastin et al, 2010;Hasan et al, 2009;Hsu et al, 2008Hsu et al, , 2010Jones et al, 2006;Lebel et al, 2008, in press;Sala et al, in press, 2005;Voineskos et al, 2010, in press). Most of these studies also show an inverse relationship (decrease followed by increase) for the mean diffusivity (MD) and link these diffusion changes to differences in microstructural organization within the WM (Dubois et al, 2008;Lebel et al, 2008).…”
Section: Introductionmentioning
confidence: 97%